Pet attachment and owner personality - Wells, Deborah L.; Treacy, Kathryn R. (Frontiers in Psychiatry, 2024)
Research points to a relationship between owner personality and strength of attachment to one's pet, with implications for psychological health. So far, studies in this area, albeit sparse, have focused on the 'Big Five' traits of owner personality. The 'Dark Triad' is a cluster of traits that has also been linked to emotional deficits, but has been overlooked in relation to pet attachment. This study therefore examined the association between owner personality and pet attachment, focusing on both the 'Big Five' and 'Dark Triad' traits of personality.Methods: A cross-sectional design was employed to collect quantitative data from dog and cat owners across the globe between May-June 2023. A purpose-designed online survey collected sociodemographic details, along with information on pet ownership, strength of the pet-owner bond and participant personality, assessed using the Big Five personality scale and the Short Dark Triad scale. The survey was fully completed by 759 dog and 179 cat owners.Results: Analysis revealed significant correlations between many of the participants' personality traits, both within and between scales. Strength of pet attachment was positively correlated with neuroticism and conscientiousness, and, more weakly, to Machiavellianism. Regression analysis revealed that females, dog owners, people over the age of 50 and individuals who had children under 18 years to care for were more strongly attached to their pets than others. Both neuroticism and conscientiousness were found to be significant predictors of participants' pet attachment scores. None of the Dark Triad traits significantly predicted the criterion.Discussion: This study points to a relationship between strength of attachment to one's pet and owner personality, at least as measured using the Big Five approach to personality assessment. There was little to support an association between the Dark Triad traits and strength of attachment to one's pet, although the link between these characteristics and attachment styles is still unknown. The investigation lends support for the idea that high attachment levels are associated with personality traits aligned to psychological ill-health. Further work is recommended in this area, with a greater focus on both strength and quality (e.g., attachment style) of the pet-owner bond.